Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1073/pnas.87.17.6698
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted basement membrane (matrigel) and laminin can enhance the tumorigenicity and the drug resistance of small cell lung cancer cell lines.

Abstract: Small cell lung cancer (SCLC) is a fatal malignancy due to its propensity to metastasize widely and to reoccur after chemotherapy in a drug-resistant form. While most SCLC cell lines are anchorage independent for growth, laminin induced the attachment of five of six SCLC cell lines tested (NCI-N417, NCI-H345, NCI-H146, NCI-H187, NCI-H510, and NCI-H209 These observations suggest that the interaction of cells with laminin as well as with other basement membrane components may play a role in tumor growth and drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
157
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 17 publications
7
157
1
2
Order By: Relevance
“…51 Coinjection with BME greatly increases the 'take' of biopsy specimens (tumorgrafts) in mice to greater than 90%. 17,18 The procedure is simple and only requires premixing of the cells with BME at 4 C (liquid BME) before injection (Fig. 3).…”
Section: Dormancy Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…51 Coinjection with BME greatly increases the 'take' of biopsy specimens (tumorgrafts) in mice to greater than 90%. 17,18 The procedure is simple and only requires premixing of the cells with BME at 4 C (liquid BME) before injection (Fig. 3).…”
Section: Dormancy Assaymentioning
confidence: 99%
“…Furthermore, BME coinjection with cancer cells will also increase the growth rate of the tumors with cells that already can form rapidly growing tumors in mice. For example, small cell lung cancer and MCF-7 cell lines were unable to form tumors in mice unless coinjected with BME, and while B16F10 melanoma cells do form growing tumors in mice when injected alone, the growth rate of the tumors can be increased several-fold when the melanoma cells are coinjected with BME 17,18,51 (Fig. 4).…”
Section: Dormancy Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for these results are unknown. Previous reports of co-injection with purified laminin have indicated that in most cases it does not enhance tumour growth, and it has been suggested that this is because of the highly soluble nature of laminin which renders it susceptible to degradation in vivo (Fridman et al, 1990). …”
Section: Resultsmentioning
confidence: 99%
“…Matrigel is composed of laminin, collagen type IV, heparin sulphate proteoglycan and entactin, along with TGF, and other growth factors which occur in the EHS tumour. Co-transplantation with matrigel has been found to enhance the growth of a range of cells in vivo including small cell lung carcinoma (SCLC), human prostatic carcinoma and human breast adenocarcinoma (Fridman et al, 1990;Pretlow et al, 1991;Noel et al, 1992).…”
mentioning
confidence: 99%